HUBUNGAN DERAJAT TROMBOSITOPENIA DENGAN MALARIA BERAT PADA PASIEN MALARIA DI RUMAH SAKIT KANUJOSO DJATIWIBOWO BALIKPAPAN - Loly R.D Siagian; Mona Zubaidah; Riski Ayu Rimadani (Jurnal Ilmiah Manuntung, 2018)
Malaria is one of the health problems in Indonesia. Kanujoso Hospital Djatiwibowo Balikpapan is a referral hospital for Balikpapan, Penajam Paser Utara and Paser. Kabupaten Penajam Paser Utara is the district with the highest incidence of malaria in East Kalimantan. In malaria there is a change of hematology one of them is thrombocytopenia. Several studies have suggested the involvement of thrombocytopenia with severe malaria events. The aim of this reasearch was to know the relations of degree of thrombocytopenia with severe malaria in malaria patients treated at Kanudjoso Djatiwibowo Hospital Balikpapan period 2013-2017. This research was conducted by using analytic observational research method with cross sectional design. The sample was taken from the patient's medical record at Kanujoso Djatiwibowo Hospital Medical Record Installation for 2013-2017 period with the sample of 81 patients. The data were analyzed by using Fisher test. The results of this research showed that distribution malaria patients based on degree of thrombocytopenia were moderate, severe and mild respectively 41,98%; 40,79% and 17,28%. Severe malaria found in 13.58% patients. We found correlation between degree of thrombocytopenia with severe malaria with Fisfer test ((p=0,043). Our study found correlation between degree of thrombocytopenia with severe malaria in malaria patientspatients at Kanudjoso Djatiwibowo Hospital Balikpapan